Improving the Ability of Subtraction Count Operations Using Abacus Media for Children with Mild Mental Disability - Adhani Indah Sari; Damri Damri (Edumaspul: Jurnal Pendidikan, 2023)
Abstract The background of this research was the discovery of a class VII mild mental retardation child at SLB Perwari Padang who had difficulty learning arithmetic subtraction operations. Based on this, a formulation of the research problem was put forward, namely "Can abacus media improve the ability of subtraction arithmetic operations for class VII mild mentally retarded children at SLB Perwari Padang?". The purpose of this study was to examine the use of abacus media on the abilities of mild mentally retarded children and to improve the ability of subtraction operations for mildly mentally retarded children. The method used in this study is an experimental method with a single subject research (SSR) approach. This study used an ABA design consisting of three conditions, namely baseline (A1), intervention, and baseline (A2). Data in this study were collected through testing and documentation techniques. The data obtained were analyzed through analysis techniques within conditions and analysis between conditions. The results showed that the subtraction arithmetic operations of the subjects in the baseline condition (A1) obtained percentages of 40%, 50%, 50%, 50%. In the intervention condition (B) the subject's abilities obtained percentages of 70%, 80%, 80%, 90%, 90%, 90%, 90%. As well as the subtraction arithmetic operation ability of the subject in baseline conditions (A2) obtained percentages of 90%, 90%, 90%, 90%. It concluded that abacus media can improve the ability of subtraction arithmetic operations for children with mild mental retardation. Keywords: Subtraction Count Operations, Abacus Media, Mild Mental Disability.